2015
DOI: 10.5173/ceju.2015.484
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in sexual function after robot-assisted radical prostatectomy: A rehabilitation program with involvement of a clinical sexologist

Abstract: IntroductionTo prospectively evaluate if the inclusion of a clinical sexologist in a penile and sexual rehabilitation program improves sexual function one year after prostate cancer surgery.Material and methodsTwelve months after da Vinci Radical Prostatectomy (dVRP) for prostate cancer, 28 fully potent (IIEF-5 >21) and sexually active men (ages 47-69 years, mean 61) who, in 2008, were enrolled in a prospectively monitored penile rehabilitation program (reference group) were compared with 79 fully potent (IIEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In our experience, during the COVID-19 pandemic, a lot of patients refused recommended sexual rehabilitation protocols. The missed or late sexual rehabilitation will possibly have an influence on future sexual function [ 14 ]. Moreover, sexual activity is considered by patients to a lesser degree because sexual needs are composed of a biological, psychological and social component [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, during the COVID-19 pandemic, a lot of patients refused recommended sexual rehabilitation protocols. The missed or late sexual rehabilitation will possibly have an influence on future sexual function [ 14 ]. Moreover, sexual activity is considered by patients to a lesser degree because sexual needs are composed of a biological, psychological and social component [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it appears that increased sexual rehabilitation efforts postoperatively improve a patient’s ability to have penetrating sexual activity one year after dVRP, with or without a nerve sparing procedure [ 19 ], and the long-term results are sustainable. Stopping sexual activity over time appears to be more related to co-morbidities, aging and change of marital status.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 19 ] reported on the positive outcome of a combined penile and sexual medicine rehabilitation program, including a clinical sexologist (CS) into the rehabilitation process, with the aim of restoring a good sexual life postoperatively for all men that were preoperatively fully potent, regardless of whether the NVB was preserved or not ( Figure 1 ). This study did not address if these patients would discontinue their sexual activity over time as patients with ED treatment alone do.…”
Section: Introductionmentioning
confidence: 99%
“…Erectile recovery should not only be focused on penile function, but also aimed to establish a satisfactory and healthy sexual life for both the patient and their partners, regardless of whether there is complete restoration of spontaneous EF. Some researchers have suggested that the application of behavioral science methods and tools by a clinical sexologist, in addition to the standard medical/surgical EF care, can improve the ability to have regular sexual activity with penetrating sex in patients undergoing robotic RP ( 67 , 68 ). Although there is a controversy in the effectiveness of penile rehabilitation modalities, any rehabilitation is undeniably better than no action at all.…”
Section: Discussionmentioning
confidence: 99%